2021
DOI: 10.1038/s41598-021-90198-3
|View full text |Cite
|
Sign up to set email alerts
|

Association of Candida albicans and Cbp+ Streptococcus mutans with early childhood caries recurrence

Abstract: Early childhood caries (ECC) recurrence occurs in approximately 40% of treated cases within one year. The association of Streptococcus mutans and Candida albicans with the onset of ECC is well known. Also, S. mutans strains harboring collagen-binding proteins (Cbps) avidly bind to collagen-rich dentin and are linked to increased caries risk. Here, we investigated the presence of Cbp+S. mutans and C. albicans in saliva and dental plaque of children with varying caries statuses, and their salivary microbiome. In… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 48 publications
3
27
0
1
Order By: Relevance
“…One explanation could be due to the difference in preferred binding sites of S. mutans and C. albicans . S. mutans adheres to the tooth surfaces and often accumulates at the carious lesion [ 32 , 33 ]. Therefore, restoring cavitated teeth reduced the binding sites for S. mutans in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…One explanation could be due to the difference in preferred binding sites of S. mutans and C. albicans . S. mutans adheres to the tooth surfaces and often accumulates at the carious lesion [ 32 , 33 ]. Therefore, restoring cavitated teeth reduced the binding sites for S. mutans in the oral cavity.…”
Section: Discussionmentioning
confidence: 99%
“…mutans antigen I/II (Yang et al ., 2018), S . mutans collagen‐binding proteins (Garcia et al ., 2021), deletion of the S . mutans delta subunit of RNA polymerase (RpoE) (Xue et al ., 2011), C .…”
Section: Candida–bacterial Biofilm‐associated Oral Diseasesmentioning
confidence: 99%
“…Among various fermentable sugars, sucrose is considered the most cariogenic (Leme et al, 2006) due to its contribution to biofilm formation and development by serving as a substrate for the production of extracellular polysaccharides (EPS) (Bowen et al, 2018). While bacteria have been traditionally considered as a major component of the aetiology of dental caries (Thomas et al, 2012;Wolff et al, 2013;Sim on-Soro and Mira, 2015), many recent studies revealed that C. albicans are often detected from plaque biofilms, particularly in children with severe early childhood caries (Hajishengallis et al, 2017;Jean et al, 2018;Xiao et al, 2018;Garcia et al, 2021). Specifically, synergistic interaction between C. albicans and cariogenic bacterium Streptococcus mutans is heavily studied in vitro and in vivo in the context of dental caries (Falsetta et al, 2014;Ellepola et al, 2017;He et al, 2017;Hwang et al, 2017;Kim et al, 2017).…”
Section: Dental Cariesmentioning
confidence: 99%
See 2 more Smart Citations